Ethno medicinal practices and traditional healing system of Kattunayakan in Tamilnadu: An anthropological study - Amuthavalluvan, *V. (International Multidisciplinary Research Journal, 2011)
This study aimed to document the traditional ethno-medicinal practices of kattunayakan of south & north arcot district, Tamilnadu focusing on their utilization of medicinal plants and associated traditional healing system. Five villages were selected out off 65 villages, the participant observation method used for collecting data. Different parts of different Plant are used to treat different ailments ranging from diseases. In an average, 60 medicinal plants and parts are as used; the diverse patterns of use of different medicinal plant parts show the considerable indigenous knowledge of kattunayakans.